Smartphone use disorder and future time perspective of college students: the mediating role of depression and moderating role of mindfulness - Yangchang Zhang; Shuai Lv; Cunya Li; Yang Xiong; Chenxi Zhou; Xuerui Li; Mengliang Ye (BMC, 2020)
Abstract Background Smartphone use disorder (SUD) of college students has drawn increasing attention. Although future time perspective (FTP) may be an important protective factor for individual SUD, the moderating and mediating mechanisms underlying this relationship remain unknown. We tested the individual roles of depression and mindfulness as moderators of this relationship. Methods A cross-sectional study was conducted in two colleges in Shandong and Chongqing in China using a sample of 1304 college students recruited by stratified cluster sampling. Data were collected through a validated self-report instrument. A moderation-mediation model was constructed, and an SPSS PROCESS macro was used to analyse the data. Results The correlation analyses showed that FTP was negatively associated with SUD of college students. The mediation model revealed that depression partially mediated the link between FTP and SUD of college students. The moderation-mediation model suggested that mindfulness moderates two direct paths: FTP to depression and depression to SUD. In the first path (FTP to depression), a high level of mindfulness among college students had weakened the relationship between FTP and depression. Here, the relationship is strengthened by a low level of mindfulness. In the second path (depression to SUD), low levels of mindfulness strengthen the link between depression and FTP. In contrast, significant association was not found with high levels of mindfulness. Conclusions Results suggest that interventions, such as improving the individual level of FTP and mindfulness, should be conducted. These interventions, in turn, help control the level of depression in college students and ultimately decrease their level of SUD.